Impact of anthropogenic activities on an urban river through a comprehensive analysis of water and sediments - Castro, María Fernanda (2021)
In this study, the aim of this study was to assess the impact of urban and industrial areas on an urban river through a comprehensive analysis of water and sediments.Six different sites along San Luis river, Argentina, were characterized by measuring 12 physical-chemical parameters and nine heavy metals according to standard protocols. Metal pollution in sediment samples was evaluated with several indices. Cluster analysis was applied to standardized experimental data in order to study spatial variability. As, Cu, Cr, Mn, Pb and Zn were the main contributors to sediment pollution, and the industrial zone studied showed moderate enrichment of Co, Cu and Zn, probably due to anthropogenic activities. Cluster analysis allowed the grouping of the sites: sediment samples were classified into two clusters according to the metal content; water samples were arranged into three groups according to organic matter content. The results were compared with sediment and water quality guidelines. They indicated progressive deterioration of water and sediment quality compared with the background area, mainly in the sites following the industrial park and domestic discharge areas. Moreover, the results showed that the analysis of both water and sediment should be considered to achieve a watershed contamination profile.